Damage-based seismic design and performance assessment of reinforced concrete structures - Wei, Jianwu (2008)
This thesis presents the research work on damage-based seismic design and performance evaluation of RC frame structures. The research involves both analytical and experimental studies. A coherent methodology is developed for damage-based design and evaluation, including the generation of damage-based inelastic spectra and the development of an implementation procedure for actual structural systems. Through a comprehensive investigation on the influences of pertinent parameters, unified empirical formulas are derived for the damage-based inelastic demand spectra. For the implementation in actual structures, two alternative methods, one based on modal pushover analysis and the other based on the characterization with a storey capacity factor, are proposed. A simple method based on a modified storey capacity factor is also developed for the prediction of the inter-storey drift distributions for performance evaluation purpose. A comparative shake table experiment is conducted on two companion frames of different detailing to investigate the damage and performance of nonseismically designed structures. The importance of evaluating the potential problems with undesired nonseismic details with respect to realistic seismic demands in low-to-moderate seismicity regions is emphasized. Furthermore, the effectiveness of a commonly used FRP repairing technique in recovering the structural performance is also investigated using shake table tests.